2017
DOI: 10.1097/mpa.0000000000000894
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating CD4+CD25+CD127low/neg Regulatory T-cells as a Prognostic Biomarker in Acute Pancreatitis

Abstract: The percentage of circulating Tregs may be implicated in the development of early immune suppression in AP. Elevated percentage of circulating Tregs at admission in AP is an independent prognostic biomarker for severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…In the present study, we found that the levels of CD4 + Foxp3 and Tregs population were significantly increased with positive correlation with the blood levels of ET, TNF-α, and IL-1β in SAP rats. The finding is inconsistent with some studies ( Ding et al, 2007 ; Pan et al, 2017 ), but is supported by others ( Xiong et al, 2012 ; Minkov et al, 2017 ). Our results indicated that the Tregs were activated under inflammatory condition and intestinal mucosal immunity was shifted from an over-inflammatory state to an immunosuppressed state in ASP rats.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the present study, we found that the levels of CD4 + Foxp3 and Tregs population were significantly increased with positive correlation with the blood levels of ET, TNF-α, and IL-1β in SAP rats. The finding is inconsistent with some studies ( Ding et al, 2007 ; Pan et al, 2017 ), but is supported by others ( Xiong et al, 2012 ; Minkov et al, 2017 ). Our results indicated that the Tregs were activated under inflammatory condition and intestinal mucosal immunity was shifted from an over-inflammatory state to an immunosuppressed state in ASP rats.…”
Section: Discussioncontrasting
confidence: 71%
“…Studies have shown that Tregs were decreased and negatively correlated with serum concentration of TNF-α and the decrease of Tregs may be responsible for uncontrolled immune activation to cause excessive inflammatory response in SAP ( Ding et al, 2007 ; Pan et al, 2017 ). However, another study has showed that the Tregs are abnormal high in SAP patients and elevated circulating Tregs is an independent prognostic biomarker for patients with ASP ( Minkov et al, 2017 ). In the present study, we found that the levels of CD4 + Foxp3 and Tregs population were significantly increased with positive correlation with the blood levels of ET, TNF-α, and IL-1β in SAP rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that >90% of Tregs with low expression of CD127 are found to express FoxP3, showing a negative correlati'on between CD127 dim+ and FoxP3 + . 15,16 On the other hand, CD127 is much more convenient to detect. Therefore, the phenotype of CD4 + CD25 str+ CD127 dim+ was used instead of CD4 + CD25 str+ FoxP3 + to identify CD4 + Tregs in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to support a shifting balance between the systemic pro-inflammatory response and the compensatory anti-inflammatory response over the early course of AP 13, 29 . It was considered that the pro-inflammatory response occurs in the first few days to weeks and that the compensatory anti-inflammatory response occurs later.…”
Section: Discussionmentioning
confidence: 99%